Law’s Practical Realization and the Challenges of Narration, Translation, Performance, and Imagination: A Symbolic Reassurance of “Juridical” Singularity? - Paim Duarte, Brisa (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)